Studi Logam Berat dalam Air dan Sedimen Kolong Retensi Kacang Pedang Pasca Penambangan Timah - Irvani Irvani; Janiar Pitulima (PROMINE, 2016)
Tin mining activities in hundred years in Bangka Island formed thousands of pond water, referred to askolong. The water from kolong has been utilized by arounds people as a source of clean water and tobe the main water resources by local water company (PDAM). Unconventional mining around kolongcaused contamination of water by heavy metals from tailing, therefore the study of heavy metals inkolong is very important to do. Data collection was done through the approach of physical andchemical parameters of water and sediment Kolong Retention Kacang Pedang. Water and sedimentphysical data collection for getting parameter of colour, flavor and smell. Chemical analysis of waterand sediment cover of Dissolved Oxigen (DO), Chemical Oxigen Demand (COD), Total DissolvedSolid (TDS) and Total Suspended Solid (TSS), pH, and the content of heavy metals usingspectrophotometer and XRF. As a result, the heavy metal composition of Fe, Cu, Pb and Cd inwater exceed the normal threshold. Element Fe in sediment has the largest number over all sample,followed by Zn, Cr, Cu, Pb and As. The metals of Cu and Zn is absent from sediment around outletarea of Kolong Retention Kacang Pedang